Conflict theory in the inculturation of the Gospel in the Nso’ of Cameroon - Nyuyki, Peter Siysi (Stellenbosch Theological Journal, 2018)
This article defines and describes conflict theory, critical theory and the views of some of their proponents, inculturation, the gospel, and Nso'. The article looks at conflict in Nso' that can be traced back to the fact that the missionaries did not understand certain aspects of Nso’ culture. Consequently, there was some conflict between Christianity and Nso' culture, particularly with ngwerong and ngiri - the core traditional social associations of the Nso' people. The article thus explains the tension that existed in the missionary era and still exists somehow today between Christianity and Nso' culture. In order to elucidate this tension, the author uses two examples: one on the encounter between one of the most dreaded masquerades and a parish priest (an early missionary in Nso' land), and the other on the main traditional social association in Nso' and the first Christians of Nso' origin. Having done that, the author outlines the incompatible activities of the traditional social associations of the Nso' people vis a vis the tenets of Christianity, showing that an understanding of these activities is necessary for the inculturation of the gospel in Nso'. In addition, the article equally shows that an understanding of the complexities and the dynamics involved in the relationship between Christ and culture is also necessary for the inculturation of the gospel. Furthermore, alluding to conflict theory and critical theory and using what he calls "consultative/dialogical"critical approach to cultural transformation, the author suggests how the tension between Christianity and Nso' culture could be curbed.